(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This scientific article examines the issues of improving the accounting and control of material assets using higher education institutions as an example. The study highlights the role of the material and technical base in the educational process and emphasizes the importance of accounting and control systems in ensuring the proper use and preservation of material resources. The paper substantiates the potential for increasing management efficiency through the digitalization of accounting processes, improvement of inventory procedures, and development of internal control mechanisms. Special attention is given to the use of accounting information in managerial decision-making and to enhancing the overall system of material asset management in higher education institutions.